2012
DOI: 10.1093/cid/cis402
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Erythema Migrans With Doxycycline for 10 Days Versus 15 Days

Abstract: NCT00910715.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 31 publications
5
50
0
1
Order By: Relevance
“…In agreement with our results, Seltzer and co-workers [ 10 ] reported that persons having suffered from LB generally did not report more symptoms than controls, including memory problems, numbness, fatigue, swollen joints, headaches, neck pain, or problems with sleeping and exercise. Also, supporting our findings, in two recent Slovenian studies of patients treated for erythema migrans, the researchers did not find any association between cases and controls in non-specific symptoms 6 months after treatment [ 15 , 16 ]. In long-term follow-up of patients with culture-confirmed LB, Wormser and co-workers did not find evidence of severe fatigue or fibromyalgia attributable to LB [ 11 , 12 ], and summary scores of physical and mental health were similar to those of the general population [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our results, Seltzer and co-workers [ 10 ] reported that persons having suffered from LB generally did not report more symptoms than controls, including memory problems, numbness, fatigue, swollen joints, headaches, neck pain, or problems with sleeping and exercise. Also, supporting our findings, in two recent Slovenian studies of patients treated for erythema migrans, the researchers did not find any association between cases and controls in non-specific symptoms 6 months after treatment [ 15 , 16 ]. In long-term follow-up of patients with culture-confirmed LB, Wormser and co-workers did not find evidence of severe fatigue or fibromyalgia attributable to LB [ 11 , 12 ], and summary scores of physical and mental health were similar to those of the general population [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…European studies have also shown that patients having suffered from early LB report a number of symptoms; however, these did not exceed the corresponding symptoms in matched controls [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In all but a few patients, the tick bites were in the closest vicinity of later BL, and EM lesions were as a rule in the area surrounding or very near BL, indicating that, like EM, BL also develops at the site of inoculation of borreliae into the skin. In the present study there was a median time interval of 21 days from the tick bite to the occurrence of BL; thus, the incubation period is longer than 14-17 days as reported for European EM [35,36]. However, BL may also appear before EM [9,33].…”
Section: Treatment Resultssupporting
confidence: 56%
“…In the United States, patients with erythema migrans can usually be treated successfully with a 10–14-day course of doxycycline, amoxicillin or cefuroxime axetil 101,137,138,143 (TABLE 1). In Europe, patients can also be treated with phenoxymethylpenicillin.…”
Section: Managementmentioning
confidence: 99%